2017
DOI: 10.1371/journal.pone.0187935
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in the marine ecosystem of two Macaronesian islands: A comparison between the remote Selvagens Reserve and Madeira Island

Abstract: The islands of Madeira and Selvagens are less than 300 km apart but offer a clear contrast between a densely populated and highly developed island (Madeira), and a largely uninhabited and remote archipelago (Selvagens) within Macaronesia in the eastern Atlantic. The Madeira Archipelago has ~260,000 inhabitants and receives over six million visitor days annually. The Selvagens Islands Reserve is one of the oldest nature reserves in Portugal and comprises two islands and several islets, including the surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…The Portuguese continental shelf is part of the northern limb of the Canary Current Upwelling System and is characterized by persistent upwelling‐type circulations during late spring and summer (Peliz et al 2002), promoting high primary productivity in the area. The archipelagos of Azores and Madeira are part of the Macaronesian biogeographical region located in the Northeast Atlantic Ocean off the coast of Europe and Africa (Friedlander et al 2017). Both archipelagos are surrounded by seamounts and are connected via oceanic currents.…”
Section: Methodsmentioning
confidence: 99%
“…The Portuguese continental shelf is part of the northern limb of the Canary Current Upwelling System and is characterized by persistent upwelling‐type circulations during late spring and summer (Peliz et al 2002), promoting high primary productivity in the area. The archipelagos of Azores and Madeira are part of the Macaronesian biogeographical region located in the Northeast Atlantic Ocean off the coast of Europe and Africa (Friedlander et al 2017). Both archipelagos are surrounded by seamounts and are connected via oceanic currents.…”
Section: Methodsmentioning
confidence: 99%
“…Selvagens have been designated by National Geographic Society as one of the pristine sites in the oceans today [25]. Human pressure is very low in Selvagens, where limited number of visitors is allowed each year.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Madeira Island is heavily populated and a high popular tourism destination. As a result of the remote location of Selvagens Islands and the high anthropogenic pressures at Madeira, total fish biomass was estimated to be 3.2 times higher at Selvagens than at Madeira, and when considering only the fish top predators biomass it reach values 10 times higher at Selvagens [26]. Previous studies describing the marine fish diversity found that 34.1% of the ichthyofauna observed in Selvagens also occurs in the Canary Islands and 47.3% in Madeira Island [27].…”
Section: Methodsmentioning
confidence: 99%
“…These phase-shifts often occur with variation in sea urchin grazing intensity (Melis et al, 2019) as their feeding activity can play a major role in the stability, biodiversity, production and functioning of these ecosystems (Duffy and Hay, 1990;Poore et al, 2009;Korpinen et al, 2010;Kraufvelin, 2017). Sea urchins can thrive at very high population densities (Lawrence, 1975;Alves et al, 2001;Gizzi et al, 2020), possess limited mobility and a powerful excavating mouth providing them the ability to regulate the distribution, abundance, and diversity of benthic marine algae communities, influencing the establishment, spread and persistence of algal species (e.g., Steneck, 2013;Filbee-Dexter and Scheibling, 2014;Friedlander et al, 2017;Melis et al, 2019). Numerous studies have unequivocally demonstrated an inverse relationship between urchin density and algal biomass as well as their role in promoting a shift of habitats with complex macroalgae forests into urchin barrens (e.g., Filbee-Dexter and Scheibling, 2014;Ling et al, 2015;Hernández, 2017;Melis et al, 2019;Pinna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%